1996
DOI: 10.1097/00007890-199611150-00003
|View full text |Cite
|
Sign up to set email alerts
|

XENOGRAFT REJECTION OF PORCINE ISLET-LIKE CELL CLUSTERS IN IMMUNOGLOBULIN- OR Fc-RECEPTOR ??-DEFICIENT MICE1

Abstract: The aim of the present study was to evaluate the role of xenoreactive antibodies in islet-like cell cluster (ICC) xenograft rejection. For this purpose, normal mice, mice with a targeted disruption of the Fc-receptor (FcR) gamma-chain, or the membrane exon of the immunoglobulin mu-chain gene, were transplanted with fetal porcine ICC under the kidney capsule. Mice lacking the FcR gamma have no functional FcR for IgG or IgE. Mice with disruption of the immunoglobulin mu-chain cannot produce antibodies, because B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 19 publications
4
30
1
Order By: Relevance
“…As mentioned above, results obtained in our previous studies [2,3,10,17,37,38,50] demonstrate that ICC xenograft rejection in rodents resembles the immune response associated with a TH1-dependent DTH-reaction with infiltration of macrophages and peripherally accumulated T cells. In contrast, other investigators have reported that eosinophils dominate the cellular response following discordant islet xenotransplantation [20, 24, 28, 42, 431.…”
Section: > Imentioning
confidence: 53%
See 2 more Smart Citations
“…As mentioned above, results obtained in our previous studies [2,3,10,17,37,38,50] demonstrate that ICC xenograft rejection in rodents resembles the immune response associated with a TH1-dependent DTH-reaction with infiltration of macrophages and peripherally accumulated T cells. In contrast, other investigators have reported that eosinophils dominate the cellular response following discordant islet xenotransplantation [20, 24, 28, 42, 431.…”
Section: > Imentioning
confidence: 53%
“…Here, we demonstrate that IL-6-deficient mice readily reject fetal porcine ICC xenografts and suggest that, in the pig-to-mouse model, the role of IL-6 in ICC xenograft rejection is minor. Several investigators have reported that eosinophils dominate the cellular response following discordant islet xenotransplantation [20,24,28,42, 431, whereas our previous studies [2,3,10,17,37,38, 501 have shown that macrophages predominate. Using a technique based on histochemical visualization of cyanide-resistant endogenous peroxidase activity for specific detection of eosinophils [45], we show that the cellular response following fetal porcine ICC xenograft rejection is dominated by F4/80+ and Mac-1' positive macrophages, and not eosinophils.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…FcR␥ Chain-deficient Mice-FcR␥ chain-deficient C57BL/6 (B6) mice have been previously described (25) and were kindly provided by Dr. Olle Korsgren (26). Normal B6 mice were used as controls.…”
Section: Methodsmentioning
confidence: 99%
“…A thymic (nu/nu) mice permanently accept fetal porcine islet-like cell cluster (ICC) xenografts (1), whereas rejection occurs within 1 week after transplantation in normal mice (2)(3)(4)(5)(6)(7). CD4…”
mentioning
confidence: 99%